Fungal colonization and ASCA/p-ANCA positivity in inflammatory bowel disease: a cross-sectional study from Turkey - Toraman, Zülal Aşçı; Öner, Pınar; Erdoğan, Meryem; Karatepe, Berçem Afşar; Şahin, Abdurrahman; Üstündağ, Yasemin; Akbulut, Handan (Journal of Infection in Developing Countries, 2026)
Introduction: Recent research indicates that individuals with inflammatory bowel disease (IBD) exhibit distinct intestinal fungal communities compared with healthy individuals. This study examined the relationship among anti-Saccharomyces cerevisiae antibodies (ASCA), perinuclear anti-neutrophil cytoplasmic antibodies (p-ANCA), and Candida spp. colonization to assess their utility in diagnosing IBD, differentiating subtypes, and predicting disease localization. Methodology: Serum samples from 240 patients with IBD and 61 healthy controls were tested for ASCA and p-ANCA using indirect immunofluorescence assay (IIFA). Fecal samples were cultured to identify Candida species. Results: ASCA positivity was significantly higher in Crohn’s disease (CD) (61.7%), whereas p-ANCA positivity was more frequent in ulcerative colitis (UC) (51.6%) (p = 0.005 and p = 0.002, respectively). Fluorescence intensity showed stronger ASCA reactivity in CD and higher p-ANCA intensity in UC. Candida colonization (? 5 CFU) was detected in 64.2% of IBD patients, with Candida albicans the most common species. Saccharomyces cerevisiae was detected exclusively in IBD patients (3.7%, p = 0.038). Higher colonization rates were observed in UC with pancolitis (78.9%) and in CD with colonic involvement (80%). ASCA intensity inversely correlated with Candida load in CD (p = 0.021), whereas p-ANCA intensity positively correlated with Candida load in UC (p = 0.038). No significant differences in Candida species diversity were observed between subtypes. Conclusions: These findings support the diagnostic value of ASCA and p-ANCA in distinguishing IBD subtypes and highlight their association with Candida colonization. Further studies are warranted to elucidate fungal antigen–antibody interactions and to refine subtype-specific diagnostic and therapeutic strategies. © 2026 Toraman et al.
Keywords: ASCA; Crohn's disease; fungal colonization; Inflammatory bowel disease; p-ANCA; ulcerative colitis